A systematic review of internet‐based information on dermatomyositis and polymyositis. (18th August 2020) - Haque, Ashraful; Cox, Miriam; Sandler, Robert D.; Hughes, Michael
Abstract: Aim: Patients with rheumatic diseases are increasingly using internet‐based information to inform healthcare utilization and make treatment decisions. Our aim was to assess the readability and quality of internet‐based information on dermatomyositis (DM) and polymyositis (PM). Method: Key words "Dermatomyositis" and "Polymyositis" were searched on 3 commonly used search engines (Google, Yahoo and Bing). The first 3 pages ( 30) of search results were examined from each search engine. Readability of information was assessed using 4 readability formulae (Flesch Reading Ease Score, Flesch‐Kincaid Grade Level, the Simplified Measure of Gobbledygook index, the Coleman‐Liau index). Quality of information was assessed using the DISCERN tool, Journal of The American Medical Association ( JAMA ) benchmark criteria and Health on The Net Code (HoN code). We also examined Google Trends ® data to determine if there were obvious temporal search patterns. Results: Thirty‐two websites were included in the study after duplicates were removed and exclusion criteria were applied. The overall quality was low including DISCERN with a median overall score of 38/80 (interquartile range 12.25), only 4/32 (13%) websites fulfilled all 4 JAMA benchmark criteria, and 9/32 (28%) had HoN code. Readability of information was assessed using 4 readability formulae (Flesch Reading Ease Score, Flesch‐Kincaid Grade Level, the Simplified Measure of Gobbledygook index, the Coleman‐Liau index. There was no obvious temporal trend in searches on analysis of Google Trends ® data. Conclusion: The overall quality and readability of internet‐based information relating to DM and PM is poor. Patients require appropriate information of high quality and readability throughout the course of their disease in order to make informed decisions on their condition including treatment.